EXTERNAL LIGHT INDUCED INCREASE OF SUPERCONDUCTIVITY OF CUPRATES - Nurimbetov, K.; Yavidov, B. (SCIENCE and SOCIETY, 2022)
In this article the effect of external light radiation on the critical temperature of superconductivity of cuprates is considered. By solving the time dependent Schodinger equation it is found that the difference of two low lying quasi-energies of the electron which is located in the double-well potential. It is shown that the temperature Bose-Einstein condensation of gas of bipolarons increases due to dependence of the difference of quasi-energies of the electron upon the frequency of external light radiation. Within the considered scenario it is satisfactorily explained observed in the experiment the effect of external light radiation on the superconducting critical temperature of cuprates.
Keywords: cuprates; high temperature superconductivity; bipolaron; Bose-Einstein condensation; Floquet formalism